Development of 3 in 1 Training Program for Making Handmade Batik in Padang Industrial Training Center - Ruva Nur Fauzia; Alim Harun Pamungkas (Universitas Negeri Padang, 2020)
This research is written based on training program 3 in 1 making handmade batik that aims to increase community skills, life skills, and create jobs in the field of embroidery and fashion. With the 3 in 1 training program for making handmade batik, the community can be creative and can distribute their potential. This study aims to illustrate how the development of a 3 in 1 training program for making batik in the Padang Industrial Training Center. The development of this program start from the planning process first, the implementation process and the program evaluation process. This research is qualitative approach with the case study method. Data collection techniques used were observation, interviews, and documentaries. From the results of the study found that the development process starts from the planning stage which includes, 1)goal setting; 2) preparation of training programs. The implementation phase includes, 1) distribution of participants' learning equipment; 2) training methods used; 3) training atmosphere; 4) and implementation of competency tests. The evaluation phase includes the initial evaluation and final evaluation stages.Keywords: Program, Development, Training, Handmade Batik